The Influence of Corporate Tax Strategy (CTS) On Consumer Reaction (Cr) With Consumer Perceived Ethicality (CPE) as A Mediating Variable Using Experimental Method - Hidayat, Kadarisman; Fatikhah Rokhimakhumullah, Dewi Noor; Cahaya Ningsih, Devi Nur; Johan Ferdhianzah, Hefry (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to examine the impact of Corporate Tax Strategies (CTSs) on consumer reactions, with Consumer Perceived Ethicality (CPE) acting as a mediating variable. Previous research on CTSs has largely focused on macro-level analyses, exploring whether aggressive tax minimization strategies lead to negative stakeholder reactions that affect company performance. However, findings on the effect of CTSs on company value remain inconclusive, with some studies reporting a negative influence and others finding no significant relationship. This research employs a quantitative approach using an experimental method to address this gap by focusing on consumer-level reactions. The methodology involves simulating scenarios to measure consumer responses to perceived ethicality in corporate tax practices. The results indicate that CTSs significantly influence consumer reactions, with CPE playing a critical mediating role. Specifically, when corporations engage in perceived unethical tax strategies, consumer trust and loyalty decline, reinforcing the importance of ethical considerations in corporate decision-making. The study concludes that incorporating ethical dimensions into tax strategies can mitigate negative consumer reactions and enhance corporate social responsibility (CSR) initiatives. These findings contribute to the literature on CSR and consumer behavior, offering practical insights for corporations aiming to align tax practices with ethical standards to foster positive consumer perceptions.